Electric-field-induced deformation caused by electroclinic and flexoelectric effects in liquid crystalline elastomer with wedge-shaped mesogens derived from cholesterol. Issue 10 (8th August 2020) - Hiraoka, Kazuyuki; Taira, Shiori; Hoshino, Yuka; Ishihara, Toshio; Yamada, Katsumi; Oshima, Masato
ABSTRACT: Mechanical responses to electric stimulation in a liquid crystalline elastomer composed of cholesterol-derived mesogens were investigated. An electric-field-induced polar deformation resembling the motion of the flukes of a dolphin was observed in the temperature region of the pseudo-isotropic state of the elastomer prepared by cross-linking reaction under splay distortion. The emergence of polarisation was also confirmed above the SmA* to the pseudo-isotropic phase transition temperature, whereas no polarisation emerged in the SmA* phase. We tentatively conclude that the flexoelectric effect within splay distortion fixed by cross-linking caused the emergence of polarisation and the polar deformation. GRAPHICAL ABSTRACT: uf0001